2019
DOI: 10.1001/jamaoncol.2018.5860
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Preexisting Antibodies in Patients Treated With Anti–PD-1 Therapy for Advanced Non–Small Cell Lung Cancer

Abstract: IMPORTANCE Administration of anti-programmed cell death protein 1 (anti-PD-1) is now standard therapy in advanced non-small cell lung cancer (NSCLC). However, immune checkpoint inhibitors, including anti-PD-1, have not been assessed in patients with subclinical disease with advanced NSCLC, and no useful clinical biomarkers have been associated with immune-related adverse events (irAEs) among these patients treated with anti-PD-1. OBJECTIVE To assess the safety and efficacy of anti-PD-1 treatment in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
245
7
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(280 citation statements)
references
References 49 publications
(66 reference statements)
17
245
7
3
Order By: Relevance
“…The development of irAEs after anti-PD-1/PD-L1 treatment has been proposed to be positive prognostic factors. 6,[30][31][32] In our study, we also found that NSCLC patients with grade 1/2 irAEs had significantly higher ORR and PFS. The occurrence of irAEs may be a sign of more robust immune response after PD-1 blockade which may lead to better treatment outcome.…”
Section: Patients Four Clusters Of Patients With Iraes Were Identifisupporting
confidence: 77%
See 1 more Smart Citation
“…The development of irAEs after anti-PD-1/PD-L1 treatment has been proposed to be positive prognostic factors. 6,[30][31][32] In our study, we also found that NSCLC patients with grade 1/2 irAEs had significantly higher ORR and PFS. The occurrence of irAEs may be a sign of more robust immune response after PD-1 blockade which may lead to better treatment outcome.…”
Section: Patients Four Clusters Of Patients With Iraes Were Identifisupporting
confidence: 77%
“…Second, although we focused on T cells, recent reports have claimed the role of B cells, autoantibodies, and serum cytokines. 5,6,9 Analysis of all peripheral blood components will be required to comprehensively understand the pathophysiology of irAEs. Third, some lateonset irAEs were observed and further investigation is required to explain the long latent period between the immunological change and clinical manifestation.…”
Section: Patients Four Clusters Of Patients With Iraes Were Identifimentioning
confidence: 99%
“…Peiro et al also reported similar ndings 17 . Although Toi et al 18,19 and Maekura et al 20 reported that thyroid peroxidase (TPO) antibody and thyroglobulin antibody (TgAb) levels before ICI therapy were predictive factors for the development of hypothyroidism, whereas our study showed no association with TPO antibody levels but suggested an association with TgAb levels (P = 0.05). Meanwhile, a high TSH level before treatment appeared to be a possible predictive factor for the development of hypothyroidism.…”
Section: Discussioncontrasting
confidence: 90%
“…Previous studies have suggested a few predictive biomarkers of irAEs in patients treated with immune‐checkpoint inhibitor. We previously reported that any pre‐existing antibodies are independent predictors of irAEs in patients with advanced NSCLC . Osorio et al found that thyroid dysfunction during pembrolizumab treatment of NSCLC is associated with antithyroid antibodies.…”
Section: Discussionmentioning
confidence: 94%